Is Generalized and Segmental Dystonia Accompanied by Impairments in the Dopaminergic System? - Ikezawa, Jun; Yokochi, Fusako; Okiyama, Ryoichi; Kumada, Satoko; Tojima, Maya; Kamiyama, Tsutomu; Hanakawa, Takashi; Matsuda, Hiroshi; Tanaka, Fumiaki; Nakata, Yasuhiro; Isozaki, Eiji (Frontiers in Neurology, 2021)
Background The pathogenesis of dystonia is remarkably diverse. Some types of dystonia, such as DYT5 (DYT-GCH1) and tardive dystonia, are related to dysfunction of the dopaminergic system. Furthermore, on pathological examination, cell loss in the substantia nigra (SN) of patients with dystonia has been reported, suggesting that impaired dopamine production may be involved in DYT5 and in other types of dystonia. Objectives To investigate functional dopaminergic impairments, we compared patients with dystonia and those with Parkinson’s disease (PD) with normal controls using neuromelanin-sensitive magnetic resonance imaging (NM-MRI) and dopamine transporter single photon emission computed tomography (DAT SPECT). Methods A total of 18, 18, and 27 patients with generalized or segmental dystonia, patients with PD, and healthy controls, respectively, were examined using NM-MRI. The mean area corresponding to NM in the SN (NM-SN) was blindly quantified. DAT SPECT was performed on 17 and eight patients with dystonia and PD, respectively. The imaging data of DAT SPECT were harmonized with the Japanese database using striatum phantom calibration. These imaging data were compared between patients with dystonia or PD and controls from Japanese database in 256 healthy volunteers using the calibrated specific binding ratio (cSBR). The symptoms of dystonia were evaluated using the Fahn–Marsden Dystonia Rating Scale (FMDRS) and the correlation between the results of imaging data and FMDRS was examined. Results The mean areas corresponding to NM in the SN (NM-SN) were 31±4.2, 28±3.8, and 43±3.8 pixels in patients with dystonia, PD, and in healthy controls, respectively. The mean cSBRs were 5.0±0.2, 2.8±0.2, 9.2 (predictive) in patients with dystonia, PD, and in healthy controls, respectively. The NM-SN area (r=-0.49, p<0.05) and the cSBR (r=-0.54, p<0.05) were inversely correlated with the FMDRS. There was no significant difference between the dystonia and PD groups regarding NM-SN (p=0.28). In contrast, the cSBR was lower in patients with PD than in those with dystonia (p<0.5x10-6). Conclusions Impairments of the dopaminergic system may be involved in developing generalized and segmental dystonia. SN abnormalities in patients with dystonia were supposed to be different from degeneration in PD.